Evaluation The Iron Homeostasis and Erythropoietic Activity in Male Rats with Anemia Related with Induced Chronic Renal Failure - Afiaa Layth Darweesh1 , Wafaa Kadhim Jasim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present study conduct to evaluation the iron homeostasis and erythropoietic activity in male rats withanemia related with induced chronic renal failure. Sixty adult male rats were divided into four groups, thefirst group administrate with DMSO as a control negative, while second group administrate DMSO andthen moringa leaf powder, third group adenine were administrated only and fourth group adenine thengiven moringaoleifera leaf powder the experiment were lasted for forty-four days. At the end of the study, blood was collected via the heart puncyure and measured the following biomarkers ( Urea , creatinine ,BBC count ,Erythropoietinerythoferrone ,, ferritin, Serum iron and hepcidin).The results revealed that therats treated adenine caused significant increase in (creatinine ,urea ,ferritin and hepcidin concentration), onethe other hand there was significantly decrease in RBC count ,PVC and HB in adenine group in additionto Erythropoietin,erythoferrone and serum iron levels , however combined adenine with moringa results inreturn these biochemical criteria to their normal levels in control group .